Review on The Multifunctional Role of Flaxseed (Linum Usitatissimum) in Pharmacotherapeutics: Bioactive Constituents and Clinical Evidence - Suraj Hirekar,; Solanke Sohani,; Katre Bhumika,; Chaudhari Tanuja,; More Ankita,; Pawar Siddhi, (Asian Journal of Pharmaceutical Research and Development, 2026)
Linum usitatissimum, commonly known as flaxseed, is one of the most important medicinal plants that has been traditionally used for its wide-ranging health and nutritional benefits. Owing to its rich chemical composition, flaxseed has attracted considerable scientific interest as a functional food with significant pharmacological potential. This review summarizes the major bioactive constituents of flaxseed, including alpha-linolenic acid, lignans, dietary fibers, proteins, vitamins, and minerals, and highlights their pharmacological relevance supported by experimental and clinical evidence. Flaxseed exhibits multiple biological activities, such as antioxidant, anti-inflammatory, estrogenic and anti-estrogenic, laxative, and antibacterial effects, which collectively contribute to its therapeutic value. Both whole flaxseeds and flaxseed oil are among the richest plant-based sources of omega-3 fatty acids, particularly alpha-linolenic acid, which plays a crucial role in maintaining cardiovascular and metabolic health. Regular consumption of flaxseeds has been associated with the prevention and management of a wide range of chronic disorders, including cardiovascular diseases, neurodegenerative conditions, obesity, diabetes mellitus, polycystic ovary syndrome, and gout. In addition, flaxseed intake has been reported to support liver and kidney function and to reduce the risk of diseases associated with oxidative stress. Its phytoestrogen content has shown beneficial effects in alleviating postmenopausal symptoms and improving bone health in osteoporosis. Furthermore, flaxseed has demonstrated positive effects in gastrointestinal disorders such as irritable bowel syndrome, diarrhea, and constipation, as well as in conditions like dry eye disease and cystic fibrosis. Notably, increasing evidence suggests that flaxseed and its bioactive components may exert protective effects against certain hormone-dependent cancers, particularly breast and prostate cancer, underscoring its importance in preventive and therapeutic healthcare strategies.